Front Cover: Magneto‐Optical Sensing Beyond the Shot Noise Limit (Adv. Quantum Technol. 1/2022). Issue 1 (4th January 2022) - Pai, Yun‐Yi; Marvinney, Claire E.; Hua, Chengyun; Pooser, Raphael C.; Lawrie, Benjamin J.
Abstract : Classical magneto‐optical microscopies are workhorse tools for materials characterization, but they are fundamentally limited in sensitivity by the photon shot noise limit. Quantum mechanical light sources guarantee that the aforementioned "standard quantum limit" is beaten. In article number 2100107, Yun‐Yi Pai, Raphael C. Pooser, Benjamin J. Lawrie, and co‐workers describe quantum enhanced magneto‐optical Kerr effect measurements that are accessible with today's quantum optical resources – an optical parametric amplifier. This approach to quantum sensing of quantum materials enables 10 nrad/√Hz sensitivity at temperatures well below 100 mK. [Cover design by Yun‐Yi Pai]